Electrowetting induced droplet jumping over a bump. (October 2019) - Merdasi, A.; Daeian, M.A.; Moosavi, A.; Shafii, M.B.
Abstract: We study electrowetting induced droplet jumping over a system consisting of a flat surface and a topographical bump mounted on the surface. Different bump shapes including triangular and elliptical configurations are considered and the results are compared with the results of the flat surface. The results indicate that droplet jumping is enhanced over the bumps and the droplet jumps to larger heights compared with the flat surface because of the lower viscous dissipation. The shape of the bump can considerably affect the droplet dynamics. Between the considered shapes the triangular bump provides a larger dynamic and the droplet on the surface with this bump can jump with larger velocity. The electrowetting number, intrinsic contact angle, droplet–ambient liquid viscosity ratio, and the Ohnesorge number have also significant effects on the jumping process. By increasing the electrowetting number, intrinsic contact angle and droplet–ambient liquid viscosity ratio, the droplet height increases. However, increasing Ohnesorge number reduces the droplet height.